The Effect of the Teaching Program on Nurses’ Practices Regarding the Implementation of Patient Care and Safety Measures during Central Venous Pressure Measurement in the Critical Care Units in Syria - Jaish, Yasser Adnan Abu (European Scientific Journal, ESJ, 2023)
The intensive care unit (ICU) is a specialized area of hospitals dealing with the diagnosis, management, and follow-up of critically ill or critically injured patients. Moreover, Critical Care Nurses (CCNs) should have strong analytical, interpersonal, and decision-making skills. Also, they need to continuously improve their knowledge, skills, and safe practice to deliver safe and effective care to their patients. Objectives: This study aimed to assess the effect of the teaching program on CCNs’ performance during the measurement of central venous pressure (CVP). Design: The quasi-experimental design was used in this study. Methods: The study was conducted from June to September 2020. This study was conducted to assess the effect of the teaching program on nurses’ performance during CVP measurement in the critical care units at Al-Assad University Hospital, Damascus. All available registered nurses (48 nurses) working in the previous ICUs during the data collection period were included in this study. An observational checklist sheet was developed by the researcher after reviewing the related literature. The duration of data collection was about three months, and each nurse was observed once for each procedure during different shifts. The researcher developed and designed the teaching program based on the nurses’ needs according to their performance during the initial assessment. This program continued for two weeks, consisting of four phases, containing workshop practices (8 hours) per day and an educational pamphlet handout. The workshop practice consists of lectures, group discussions, and training scenarios. Every nurse must attend the training sessions daily, for at least one hour. Results: The results showed that the level of knowledge and practice of the studied nurses in CVP measurement was average and poor before the teaching program and the nurse’s level improved after the program. There was a variation of improvement regarding the nurses’ age, qualifications, and experience. The best performance was for nurses in the age group between 20-24 years, nurses with a master’s degree, and nurses with less than five years of experience. Overall, this study found a statistically significant relationship before and after the implementation of the educational program (p<0.001). Conclusion: There has been an obvious improvement in nurses’ knowledge and performance after the teaching program about age, qualifications, and experience in all selective procedures. It is essential to help nurses to expand their knowledge and practices to provide high-quality care and promote patient safety.